Beispiel Nr: 02
$ \text{Gegeben:} \\ \vec{a}=\left( \begin{array}{c} a_1 \\ a_2 \\ a_3 \\ \end{array} \right)\qquad \vec{b}= \left( \begin{array}{c} b_1 \\ b_2 \\ b_3 \\ \end{array} \right) \qquad \vec{c}= \left( \begin{array}{c} c_1 \\ c_2 \\ c_3 \\ \end{array} \right) \\ \text{Gesucht:} \text{Spatprodukt,lineare Abhängigkeit,Basisvektoren} \\ \\ \textbf{Gegeben:} \\ \vec{a} =\left( \begin{array}{c} 3 \\ -4 \\ 7 \\ \end{array} \right) \qquad \vec{b}= \left( \begin{array}{c} -3 \\ 7 \\ 2 \\ \end{array} \right)\qquad \vec{c}= \left( \begin{array}{c} 4 \\ 2 \\ 2 \\ \end{array} \right) \\ \\ \textbf{Rechnung:} \\ \vec{a}= \left( \begin{array}{c} 3 \\ -4 \\ 7 \\ \end{array} \right) \qquad \vec{b}= \left( \begin{array}{c} -3 \\ 7 \\ 2 \\ \end{array} \right) \qquad \vec{c} = \left( \begin{array}{c} 4 \\ 2 \\ 2 \\ \end{array} \right) \\ V=\left|\begin{array}{ccc} 3\ & -3 & 4\\ -4& 7 & 2\\ 7& 2 & 2 \\ \end{array}\right| \begin{array}{cc} 3\ & -3 \\ -4& 7 \\ 7& 2 \end{array} \\ V=3 \cdot 7 \cdot 2+ \left(-3\right) \cdot 2 \cdot 7 + 4 \cdot \left(-4\right) \cdot 2 \\ - 4 \cdot 7 \cdot 7 - 3 \cdot 2 \cdot 2 - \left(-3\right) \cdot \left(-4\right) \cdot 2 \\ V=-264 \\ \text{Die 3 Vektoren sind linear unabhängig - Basisvektoren} $